Genetic and Genomic Analysis of the Tree Legume Pongamia pinnata as a Feedstock for Biofuels. Issue 3 (1st November 2013) - Biswas, Bandana; Kazakoff, Stephen H.; Jiang, Qunyi; Samuel, Sharon; Gresshoff, Peter M.; Scott, Paul T.
Abstract : The tree legume Pongamia { Pongamia pinnata (L.) Pierre [syn. Millettia pinnata (L.) Panigrahi]} is emerging as an important biofuels feedstock. It produces about 30 kg per tree per year of seeds, containing up to 55% oil (w/v), of which approximately 50% is oleic acid (C18:1 ). The capacity for biological N fixation places Pongamia in a more sustainable position than current nonlegume biofuel feedstocks. Also due to its drought and salinity tolerance, Pongamia can grow on marginal land not destined for production of food. As part of the effort to domesticate Pongamia our research group at The University of Queensland has started to develop specific genetic and genomic tools. Much of the preliminary work to date has focused on characterizing the genetic diversity of wild populations. This diversity is reflective of the outcrossing reproductive biology of Pongamia and necessitates the requirement to develop clonal propagation protocols. Both the chloroplast and mitochondrial genomes of Pongamia have been sequenced and annotated (152, 968 and 425, 718 bp, respectively), with similarities to previously characterized legume organelle genomes. Many nuclear genes associated with oil biosynthesis and nodulation in Pongamia have been characterized. The continued application of genetic and genomic tools will support the deployment of Pongamia as a sustainable biofuel feedstock.